Ataxia‐telangiectasia mutated (ATM) participates in the regulation of ionizing radiation‐induced cell death via MAPK14 in lung cancer H1299 cells - Liang, Nan (Cell Prolif, 2015)
OBJECTIVES: The role of Ataxia‐telangiectasia mutated (ATM) in response to DNA damage has previously been studied, but its underlying mechanisms specific to ionizing radiation (IR) have remained to be elucidated. In this study, function of ATM on radiation‐induced cell death in lung cancer H1299 cells was analysed. MATERIALS AND METHODS: Human lung cancer cells, H1299, were used, and cell models with ATM (−/−) and MAPK14(−/−) were established by genetic engineering. Radiosensitivity was analysed using colony formation assays. Western blotting and co‐immunoprecipitation were implemented to detect protein expression and interaction. MDC staining and GFP‐LC3 relocalization were used to detect autophagy. RESULTS: Autophagy as well as phosphorylation of ATM was activated by ionizing radiation. Both the inhibitor of ATM, KU55933 and ATM silencing reduced phosphorylation of ATM and MAPKAPK2 expression. Both ATM (−/−) and MAPK14(−/−) cells displayed hypersensitivity. IR increased autophagy level by more than 129% in DMSO‐treated cells, while only by 47% and 27% in KU55933‐treated and ATM (−/−) cells respectively. MAPK14 knock‐down alone gave rise to the basal autophagy level, but decreased notably after IR. KU55933 and ATM knock‐down inhibited IR‐induced autophagy by activating mTOR pathways. Both Beclin1–PI3KIII and Beclin1–MAPKAPK2 interactions as were remarkably affected by silencing either ATM or MAPK14. CONCLUSIONS: ATM promoted IR‐induced autophagy via the MAPK14 pathway, mTOR pathway and Beclin1/PI3KIII complexes. MAPK14 contributed to radiosensitization of H1299 cells.